2000
DOI: 10.1111/j.1348-0421.2000.tb02519.x
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Expressed phoP Inhibits Mouse‐Virulence of Salmonella typhimurium in an Spv‐Dependent Manner

Abstract: In Salmonella typhimurium, the transcription of several virulence genes including spvB is regulated by the PhoP/PhoQ regulatory system. To further examine the relationship between the PhoP/PhoQ and Spy systems for virulence in mice, we examined a non-polar phoP mutation combined with different virulence plasmid genotypes for effects on virulence of S. typhimurium in the mouse model. PhoP-/Spv+ and PhoP-/ Spv-mutants were not detectably recovered from the spleens of subcutaneously or orally inoculated mice. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…We used three isogenic strains of S. typhimurium SR-11 in this study: Spv-r-the spv genes containing wildtype (X3306) (11,12,21); PhoP"-Spv+ containing phoi" (X3306 pPhoP) (22); and Spv -a deletion of spvRABCD replaced by the tet gene of pBR322 (UFllO) (21,22). Histological analysis was performed as described previously (21).…”
Section: Centrations (8)mentioning
confidence: 99%
See 2 more Smart Citations
“…We used three isogenic strains of S. typhimurium SR-11 in this study: Spv-r-the spv genes containing wildtype (X3306) (11,12,21); PhoP"-Spv+ containing phoi" (X3306 pPhoP) (22); and Spv -a deletion of spvRABCD replaced by the tet gene of pBR322 (UFllO) (21,22). Histological analysis was performed as described previously (21).…”
Section: Centrations (8)mentioning
confidence: 99%
“…2). We previously reported that the constitutive expression of phol" leads to a decrease in the splenic CFU values of the Spv" but not of the Spv S. typhimurium after oral or subcutaneous inoculation of mice (22). In the present study, splenic CFU values at day five after oral inoculation or at day four after subcutaneous inoculation were as follows: Spv ' (oral), log J04.9±0.4 (n=9); PhoP" (oral), log I03.3±0.6 (n=7); Spv Toral), log J02.9±0.9 (n=9); Spv" (subcutaneous), log J07.5±0.3 (n=6); PhoP" (subcutaneous), log J06.0 ± 0.8 (n = 8); and Spv Tsubcutaneous), log J05.2±0.1 (n=9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To observe in vivo transfer of plasmid and immune induction, S. typhimurium harboring plasmid was orally administered [5]. Mice were deprived of drinking water and food for 5-6 h prior to the administration, and fed 30 min after the infection.…”
mentioning
confidence: 99%
“…Stocker, Stanford University. S. typhimurium phoPdeficient strainχ3306 phoP {phoP:: aphT ∆Ter} [5] and rpoE-deficient strainχ3306 rpoE {rpoE:: aphT} [10] were derivatives of strain SR-11. All bacteria were routinely grown in Luria-Bertani (LB) broth [1% Bacto tryptone (Difco Laboratories, MI, USA) 0.5% Bacto yeast extract (Difco Laboratories) 1% sodium chloride (Nacalai Tesque, Kyoto, Japan)] or on an LB agar plate at 37°C.…”
mentioning
confidence: 99%